MODEL OF SEMANTIC INTEGRATION OF INFORMATION SYSTEMS PROPERTIES IN RELAY DATABASE REENGINEERING PROBLEMS - Oleg Avrunin; Oleksiy Vlasov; Valentin Filatov (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of research is methods of semantic integration of subject areas of heterogeneous information systems and distributed databases. This class of systems are created on the basis of database technologies, are widespread and used in all areas of economic activity. Such systems are characterized by high complexity of design, maintenance and modification. The purpose of the research is the development of a subject area model based on the semantic properties and relationships of data elements; development of effective technology of integration of information resources of heterogeneous computer systems on the basis of technology of management of database systems; research and formalization of classes of inhomogeneity of data structures aimed at solving the problem of determining the types of information objects. Development of tools for the design and maintenance of application problems for the integration of heterogeneous information systems and distributed databases. Results: the analysis of existing methods and models of integration of subject areas on the basis of semantic properties and connections of data elements is carried out;  developed an effective mathematical model, technology and algorithm for semantic integration of information resources of heterogeneous computer systems for relational databases;  investigated and formalized classes of inhomogeneity of data structures aimed at solving the problem of determining the types of information objects;  the model is developed and means of the logical description of properties of information objects for definition of border of the considered subject area are investigated. Conclusion: the article considers a formalized infographic model of the subject area, which focuses on the semantic relationships between information objects of databases. An axiomatic approach to the description of the subject area is formulated, which allows to consider the problem of modeling the relations of the elements of the subject area in the form of a set of rules that determine the existence of data elements. On the basis of the analysis of structures and models of databases of information systems the general approach to construction of the universal technology focused on the decision of problems of management of heterogeneous information resources of computer systems is defined.